IgE to epitopes of Ara h 2 enhance the diagnostic accuracy of Ara h 2‐specific IgE. Issue 9 (23rd April 2020) - Santos, Alexandra F.; Barbosa‐Morais, Nuno L.; Hurlburt, Barry K.; Ramaswamy, Sneha; Hemmings, Oliver; Kwok, Matthew; O'Rourke, Colin; Bahnson, Henry T.; Cheng, Hsiaopo; James, Louisa; Gould, Hannah J.; Sutton, Brian J.; et al.
Abstract: Background: Understanding the discrepancy between IgE sensitization and allergic reactions to peanut could facilitate diagnosis and lead to novel means of treating peanut allergy. Objective: To identify differences in IgE and IgG4 binding to peanut peptides between peanut‐allergic (PA) and peanut‐sensitized but tolerant (PS) children. Methods: PA (n = 56), PS (n = 42) and nonsensitized nonallergic (NA, n = 10) patients were studied. Synthetic overlapping 15‐mer peptides of peanut allergens (Ara h 1‐11) were spotted onto microarray slides, and patients' samples were tested for IgE and IgG4 binding using immunofluorescence. IgE and IgG4 levels to selected peptides were quantified using ImmunoCAP. Diagnostic model comparisons were performed using likelihood‐ratio tests between each specified nominal logistic regression models. Results: Seven peptides on Ara h 1, Ara h 2, and Ara h 3 were bound more by IgE of PA compared to PS patients on the microarray. IgE binding to one peptide on Ara h 5 and IgG4 binding to one Ara h 9 peptide were greater in PS than in PA patients. Using ImmunoCAP, IgE to the Ara h 2 peptides enhanced the diagnostic accuracy of Ara h 2‐specific IgE. Ratios of IgG4/IgE to 4 out of the 7 peptides were higher in PS than in PA subjects. Conclusions: Ara h 2 peptide‐specific IgE added diagnostic value to Ara h 2‐specific IgE. Ability of peptide‐specific IgG4 to surmount their IgE counterpart seems to be important in established peanut tolerance. Abstract : This study identifies differences in IgE and IgG4 binding to peanut peptides between peanut‐allergic and peanut‐sensitized children. Peanut peptide microarray analyses reveal that seven peptides on Ara h 1, Ara h 2 and Ara h 3 are bound more by IgE of peanut‐allergic compared to peanut‐sensitized patients. Measuring IgE to the Ara h 2 peptides in combination with Ara h2 enhances the diagnostic accuracy of Ara h 2‐specific IgE. Abbreviation: PPV, positive predictive value